Parents' involvement in children's education from geographical perspectives - Rosmadi Fauzi,; Saiful Adli Suhadak,; Veronica Sayu Balang,; Muhammad Fathi Marzuki,; Qhaiyyum Azhar Ramli,; Kamaruzaman Jusoff,; Tengku Adeline Adura Tengku Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Parental involvement has been recognized as a crucial factor in children’s academic achievement. Due to more challenges in the education system nowadays, parents have most responsibility for their children’s education. Parents need to demonstrate a strong commitment and support by assisting with home learning, interacting with teachers, and attending programmes organised by the school. However, the extent and nature of parental involvement are significantly influenced by parents' demographic and geographical contexts. This study aimed to investigate the relationship between parental involvement in children's education and seven geographical factors: housing size, population density, sub-district size, residential location, school location, land use, and distance between home and school. The study involved 400 parents of primary school children in Kuala Langat district using the chi-squared test. Data is collected quantitatively and analysed using SPSS version 26 software. Result indicates that there was a relationship between parents' involvement and geographical factors. Therefore, the study is expected to guide parents, teachers, and schools to help with children's education based on geographical factors. Future works may focus on parental involvement and socio-economic factors to gain a deeper insight into parental involvement in children’s educational development. A more nuanced understanding of this relationship would offer a more comprehensive perspective on parental involvement in children's educational development.